2012
DOI: 10.1177/0276146712440708
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, Consumer Tensions, and the Shaping of Consumer Culture in India

Abstract: The authors examine consumer tensions arising in India’s transitional marketplace. These findings uncover cultural characteristics underlying consumption strategies to address these tensions: the danger and immorality of consumption, the distance and inaccessibility of many newly available products, and the desire for sociality and relationships via consumption. Consumer desires sometimes are in opposition to and sometimes in line with local cultural values and norms such as the frugality ideal and Indian ritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 40 publications
0
64
0
Order By: Relevance
“…Additionally, the definition of 'middle-class' as a category is highly contested. For example, definitions are often based on factors such as: earning an annual income over 70,000 rupees (Guha, 2007 in Eckhardt andMahi, 2012); speaking English and having private education (Murphy, 2011); appetite for global culture and western lifestyles (Chaudhuri and Majumdar, 2006;Mawdsley, 2004:85); and/or being constituted in opposition to imagined categories of the slum-dwelling or rural poor (Nandy, 1998). However it is defined, the consumption practices of the middle-class and whether these practices may result in increased ethical/responsible consumption are of great interest.…”
Section: Consumers and Crm In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the definition of 'middle-class' as a category is highly contested. For example, definitions are often based on factors such as: earning an annual income over 70,000 rupees (Guha, 2007 in Eckhardt andMahi, 2012); speaking English and having private education (Murphy, 2011); appetite for global culture and western lifestyles (Chaudhuri and Majumdar, 2006;Mawdsley, 2004:85); and/or being constituted in opposition to imagined categories of the slum-dwelling or rural poor (Nandy, 1998). However it is defined, the consumption practices of the middle-class and whether these practices may result in increased ethical/responsible consumption are of great interest.…”
Section: Consumers and Crm In Indiamentioning
confidence: 99%
“…Whether middle-class consumers in India will prioritize ethical consumption or focus more heavily on the conspicuous consumption of branded products remains to be seen. According to Chaudhuri and Majumdar (2006) and others, Indian consumer culture before liberalization in 1991 was dominated by the Gandhian philosophy of simple living and self-sacrifice as well as by the anti-materialistic religious messages of Buddhism and Hinduism and the community-oriented messages of socialism (see also Eckhardt and Mahi, 2012;Khare, 2011). After liberalization conspicuous consumption by individuals of branded products (particularly western ones, such as P&G brands) began to dominate.…”
Section: Consumers and Crm In Indiamentioning
confidence: 99%
“…Similar to Indian consumers in Eckhardt and Mahi's (2012) study, we were able to self-regulate our consumption practices in some of the areas for which we had strong values.…”
Section: Self-regulationmentioning
confidence: 63%
“…Changes in consumption norms over time due to age or life-cycle stages, technological changes, social or economic transformations and globalization have been studied in diverse fields such as marketing, economics, sociology, anthropology, geography and history (e.g., Schiffman and Kanuk, 2009;Shove, 2003;Trentmann, 2004;Clarke, 2008;Eckhardt and Mahi, 2012;Jackson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…He further highlights that markets may also affect religion with market offerings sometimes causing conflict over what is right or wrong, in the religious sense, for a believer, and even causing a re-evaluation of that believer's faith. This topic is the subject of Eckhardt and Mahi's (2012) paper on the consumer tensions caused by an increasingly globalized marketplace in India. They found that Hindu religious ideals helped some consumers manage -or even resist altogether -the desires created by consumer culture.…”
Section: Religious Authoritymentioning
confidence: 99%